Enhancing Fluoride: Clinical Human Studies of Alternatives or Boosters for Caries Management - Fontana, Margherita (Caries research, 2016)
Dental caries remains a major public health problem, especially for certain high-risk population groups. The goal of this study was to assess the evidence regarding strategies meant to be used as alternatives or booster/supplements to fluoride for caries prevention and management. Articles were selected for inclusion if they had a prospective longitudinal design, with a fluoride control arm, and were conducted in human subjects. Of the included studies, 7/18 studies on calcium-based strategies favored the test product (the majority of studies included exposure of fluoride in all groups). All the arginine studies (8/8) included a combination of arginine and a calcium base, and concluded that this has the potential to significantly boost the performance of fluoride. The remaining included studies focused on the addition of microbial-related strategies to a fluoride-containing vehicle (2 xylitol studies and 1 study using a probiotic milk), and all favored the combination as a booster to fluoride. Thus, the current study did not identify evidence for any strategy to effectively be used as a substitute or alternative to fluoride, but identified some consistent evidence derived from the use of prebiotic strategies (primarily from use of arginine combined with calcium) to support their potential use to boost the mechanism of action of fluoride. Thus, fluoride-based strategies remain the standard for caries prevention and management, with some evidence that boosting the effects of fluoride by the use of prebiotic strategies is a promising possibility.